The game changer in French football: the case of Paris St. Germain - Mirkovic, G.; Sauer, T.; Zülch, H. (Soccer & Society, 2025)
In 2011, French football experienced a defining moment when Qatar Sports Investments acquired a majority stake in Paris St. Germain (PSG). The initial €30 million investment was one of many investments made by wealth funds from the Gulf States in European football, but only a few have had such a transformative effect. The investment in the club was the starting point that led to the rise of PSG becoming the leading football club in France. This paper is the first to examine the investment in light of true value creation from PSG`s and QSI`s perspectives. The review of its sporting, economic, social, and media capital reveals that PSG`s sporting success and initiation of a global brand came with a high cost but generated indirect returns for QSI. Ultimately, QSI`s long-term commitment might capitalize with Arctos` co-investment in December 2023.